伝統的医療行動の医療人類学的研究 - 樋口 まち子 (Kokusai Hoken Iryo (Journal of International Health), 2006)
IntroductionFolk medicine is practiced in most countries for the purpose of treating illnesses, preventing from ailments and promoting health. When people immigrate, they bring and practice their medical experience and knowledge in the new country. They integrate their culture and traditional medical practices to those of their new home country.MethodsForty five foreigners from three different countries i.e. China, Philippine, Brazil, living in Japan were interviewed in-depth, in order to compare the differences of their traditional health behavior.ResultsThe results show that Chinese have more knowledge, practice traditional health behavior more and suffer less from ailments than Philippinos and Brazilians, during the one year period prior to the date of interview. Most respondents practice traditional health behavior for health promotion and prevention from ailments while they chose either traditional or modern medicine for treatment according to the symptoms or diseases. All respondents consciously took certain drinks for promoting and maintaining their health. Only Chinese practice the "hot-cold" classification in illness management and diet. The concepts of opposition and balance are only some of the several approaches used in treating illnesses. Philippinos and Chinese use traditional health practices for maternal and child care more than Brazilians. More than 30% of Philippinos suffered from severe morning sickness and 20% of them gained excess weight rapidly during pregnancy. Respondents from all three countries took special traditional meals to recover from tiredness and produce adequate breast milk after childbirth.ConclusionsAll three different groups have integrated their own traditional health behavior to the Japanese life style not only for promotion and prevention from illnesses but also to complement medical services in Japan. It was found that some traditional practices were in common and others were very unique among the three countries. Suggestions for further research are made. 目的：世界各地で人々は疾病の治療や健康の維持増進のために複数の医療システムを発展させ、居住地が変わっても、独自の民俗的健康行動を持続してきた。日本では、1990年以降、ニューカマーと呼ばれる外国人住民が増加し、家族を形成して定住する傾向も強まっている。彼らは様々な健康問題に直面した際に、日本の保健医療サービスを活用すると同時に、独自の民俗的健康行動を実践していることが予測されるが、その実態が充分に把握されているとは言い難い。そこで、中国、フィリピン、ブラジル出身者を対象に出身国ごとの文化的相違を把握し、健康の維持増進や疾病予防に対する民俗的健康行動の実践状況を比較考察した。方法：静岡県内のフィリピン人21人、中国人17人、ブラジル人7人の合計45人の女性を対象に、個別インタビューを実施し、得られたデータをコード化してインタビューガイドラインに沿って分析した。結果：配偶者が日本人で長期在留しているフィリピン人が過去1年間の罹患者の割合が最も高く、特に、来日後、花粉症や喘息、膠原病やバセドウ氏病に罹患したものもおり、これらの疾病の対処行動には、夫の経済状況及び医療機関の状況が大きな影響を及ぼしていた。さらに、3ヵ国の出身者はいずれも、日常的に食事を重要視していたが、特に中国人は、「医食同源」という認識を強くもち、食物を属性に分類して母国の食材と日本の食材を組み合わせて、健康的な食生活の維持に努めるとともに、時間、季節、体調に合わせた食生活を形成していた。また、妊娠・出産・育児に関しては、3ヵ国の出身者が体調の回復や母乳分泌促進のために、母国でも良いとされている食物を意識的に摂取していた。特に、中国人及びフィリピン人が、母国に戻って出産することを含め、伝統的習慣を幅広く保持していた。結論：研究対象者の年齢、在日期間、在日理由、宗教の違いにかかわらず、母国の伝統医療及び民俗医療に基づく生活習慣を維持していたが、特に、健康の維持増進のために意識的に食生活のあり方に注意を払っている中国人がフィリピン人及びブラジル人と比較して、過去1年間の罹患者の割合が最も低かった。また、妊娠・出産・育児の時期には、フィリピン人と中国人が民俗的健康行動を実践していた。今後は、研究対象者の文化や習慣及び出身国の伝統的・民俗的健康行動の実態に関する詳細な把握と、それらの健康状態との因果関係をさらに探求することによって、外国人住民の文化や習慣を視野に入れた、生活全般を包括的に把握した保健医療サービスの充実の一助になることが期待される。